The Effect of Interval Training and Rope Skipping on the Results of Increased Vo2 Max in Futsal Extracurricular Students - Padillah, Ade; Komaludin, Dudi; Giovanni, Krisno; Hilmy, Faris; Putra, Jeki Purnama (JUMORA: Jurnal Moderasi Olahraga, 2025)
This research aims to determine: (1) the effect of interval training on improvement VO2 max; (2) the influence of rope skipping training for increasing VO2 max; (3) Which is more effective between interval training and rope skipping training in increasing VO2 max for MA Nurul Hadid futsal extracurricular students in the Cirebon Region, West Java. This inquire about was conducted utilizing an exploratory strategy with a two-group pretest-posttest plan. The populace in this consider were 26 futsal extracurricular understudies. The examining procedure is purposive inspecting. The test in this think about was 20 futsal extracurricular understudies at MA Nurul Hadid Cirebon with 16 medicines given. The investigate instrument utilized the Multistage Wellness Test. The information examination strategy utilized in this investigate is the t-test to decide the comparison of interim preparing and rope skipping preparing in expanding VO2 max. Based on the inquire about comes about are as takes after. (1) There's an impact of expanding VO2 max for extracurricular futsal understudies at MA Nurul Hadid with interim preparing, which is demonstrated by the calculated t esteem (6.419) > t table (2.262). (2) There's an impact of expanding VO2 max for MA Nurul Hadid futsal extracurricular understudies with rope skipping preparing, which is demonstrated by the calculated t esteem (3.335) > t table (2.262). (3) Interim preparing and rope skipping preparing are similarly great for expanding VO2 max in futsal extracurricular understudies MA Nurul Hadid since there was no critical contrast in comes about, which was demonstrated by the calculated t esteem (1.870) < t table (2.101)